Thermodynamic Study of Palm Kernel Shell Gasification for Aggregate Heating in an Asphalt Mixing Plant - Firman Asto Putro; Sunu Herwi Pranolo; Joko Waluyo; Ary Setyawan (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
This study evaluated thermodynamically the performance of conversion of palm kernel shells into combustible gas through gasification technology for aggregate heating in a hot-mixed asphalt production plant by developing a thermodynamic model using licensed Aspen Plus v.11 software. The effects of the equivalence ratio (ER) in the gasification process and the amount of combustion air to combustible gas to attain the required aggregate temperature were investigated. The thermodynamic model showed a good agreement with the experimental results based H2 and CO contain in producer gas which provided by maximum root mean square errors value of 8.82 and 6.42 respectively. Gasification of 30–35 kg of palm kernel shells in a fixed-bed gasifier reactor using air as a gasifying agent at an ER of 0.325–0.350 generated gaseous fuel for heating 1 ton of aggregate to a temperature of 180–200°C with combustion excess air 10%–20%.